FAKTOR EKTERNAL YANG MEMPENGARUHI REMAJA MENYALAHGUNAKAN OBAT TRAMADOL DI DESA AURCINO KABUPATEN TEBO - Iqbal, Yan - (Pendidikan Sosiologi, 2014)
This thesis aims to describe external factors that influence teenagers to misapply tramadol medicine in aur cino village VII koto subdistrict tebo regency. From the problem that is researched there are 10 teenagers misapply tramadol. Tramadol is a kind of medicine has indication to cure critical agonies and heavy chronic. Research method that is used in arranging this thesis is a method that uses approach qualitative research and type that is used is descriptive. Whereas research informant selection uses snowball sampling technique. Theory that is used in this research is Differensial Association theory according to Edwin H Shuterlad. The result shows that external factors that influence teenagers misapply tramadol in aur cino village VII koto subdistrict tebo regency can be grouped as follows: (1) factors that come from family environment. (2) factors that come from environment. (3) factors that come from no rules about selling medicine and alcohol drinking in society.